A Study on Shock Absorbing Properties of Airbags - SAIJO, Eri; KEMMOCHI, Kiyoshi; BAO, Limin; QIAN, Danna; TAKATERA, Masayuki (Nihon Kikai Gakkai ronbunshū. A, 2008)
The promise of airbags for crew protection when automobiles collide has been realized. In previous airbag development, the prevailing purpose has been to protect the lives of the automobile's crew. It is necessary to understand in detail, as basic data, the impact of the airbag upon the crew, the crew's physique, and the specific accident situation, in order to minimize injuries due to airbag inflation for various accident situations and crews. There are two kinds of impact contact phenomena between the airbag and the crew. One occurs when the airbag is inflated then contacts the crew. The other occurs when the crew collides with the already inflated airbag. We focused our attention in the latter case in this research, designing an experiment apparatus based on a model of the airbag and the crew. The impact force is measured when the airbag contacts the crew under various conditions. The shock-absorbing characteristics of the airbag depend on the fabric's mechanical properties and contact conditions.